Cultivating Critical Minds: Interdisciplinary Strategies for Empowering University Students Against Online Gambling Propaganda - Siricharoen, Nattanun (Community and Social Development Journal, 2024)
In this qualitative study on "Cultivating Critical Minds: Interdisciplinary Strategies for Empowering University Students against Online Gambling Propaganda," researchers have uncovered critical insights from experts spanning fields like Psychology, Public Health Science, Communication Arts, Law, and Information Technology. Conducted between December 2022 and January 2023, this research brings to light several key findings: 1) Lack of Awareness and Understanding: A significant issue is the lack of awareness among university students regarding the risks associated with online gambling. This knowledge gap can lead to adverse consequences such as depression and financial distress. Experts emphasize the need to educate students about the intricacies of online media and digital platforms to address this challenge. 2) Role of Mass Media and Regulation: Mass media has a paradoxical role in promoting gambling while failing to educate students about its risks. Experts recommend vigilant monitoring of online gambling sites, identifying suspicious transactions, and collaborative efforts with law enforcement agencies to combat this issue. Building public awareness and collective immunity against online gambling propaganda is also crucial. 3) Addressing Root Causes: The study identifies various factors pushing university students towards online gambling, including societal influences, economic pressures, family dynamics, and lax law enforcement. Experts advocate for a comprehensive approach to mitigate these underlying issues, such as promoting positive peer influences, delivering financial literacy education, reinforcing family values, providing counseling services within educational institutions, and implementing stricter legal measures. 4) Treating Gambling Addiction: A holistic strategy is presented for combating gambling addiction, focusing on trust-building, critical thinking cultivation, experiential learning, life skills development, and promoting acceptance and understanding. These measures aim to help adolescents recognize the consequences of their actions. 5) Legal Framework and Education: Urgent reforms are needed in the legal framework to effectively combat online gambling. Proposals include clear definitions, supplementary laws targeting media platforms, and comprehensive educational campaigns highlighting the risks of online gambling. Experts also recommend studying the public relations strategies employed by gambling media platforms and developing online gambling media literacy programs. In summary, this research underscores the need to address the pervasive influence of online gambling propaganda among university students. It advocates for a comprehensive, interdisciplinary approach that involves education, regulation, and addressing root causes to protect vulnerable populations. Implementing these recommendations has the potential to create a safer online environment for students and empower them with the critical tools needed to make informed choices.